2019
DOI: 10.1101/638007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Branched-Chain Amino Acid Metabolic Reprogramming Orchestrates Drug Resistance to EGFR Tyrosine Kinase Inhibitors

Abstract: 26 2 SUMMARY 27 Drug resistance is a significant hindrance to effective cancer treatment. Although 28 resistance mechanisms of epidermal growth factor receptor (EGFR)-mutant cancer cells to 29 lethal EGFR tyrosine kinase inhibitors (TKI) treatment have been investigated intensively, 30 how cancer cells orchestrate adaptive response under sublethal drug challenge remains 31 largely unknown. Here we find that 2-hour sublethal TKI treatment elicits a transient 32 drug-tolerant state in EGFR-mutant lung cancer cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…BCAT1 in particular is associated with cancer cell growth and has been proposed as a prognostic cell marker. 66,68,69 In addition, many studies have explored BCAT1 as a potential target for cancer therapeutics, as it is also linked to cell proliferation via m-Torc1 activity. 70 BCAA metabolism has been shown to alter gene expression in cancer cells by altering the epigenome.…”
Section: Discussionmentioning
confidence: 99%
“…BCAT1 in particular is associated with cancer cell growth and has been proposed as a prognostic cell marker. 66,68,69 In addition, many studies have explored BCAT1 as a potential target for cancer therapeutics, as it is also linked to cell proliferation via m-Torc1 activity. 70 BCAA metabolism has been shown to alter gene expression in cancer cells by altering the epigenome.…”
Section: Discussionmentioning
confidence: 99%
“…BCAT1 expression is confirmed to be associated with cancer progression in various solid tumors [4][5][6][7][8][9]27 , including cervical cancer 10 and HCC 12 . Increased BCAT1 expression correlates with the chemotherapeutic agent resistance 3,9,13 . For instance, Cho et al 3 reported that BCAT1 promoted IDH1 wild-type glioblastoma multiforme cell proliferation, invasion and increased resistance to bevacizumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhu et al 9 found that miR-218 increased chemosensitivity to cisplatin by targeting BCAT1 in prostate cancer. Moreover, Wang et al 13 showed that BCAT1 conferred sublethal tyrosine kinase inhibitor resistance in EGFR-mutated lung cancer cells through the H3K9 demethylation-mediated BCAA metabolism reprogramming. The above findings confirm the important role of BCAT1 in tumor drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,9 Targeting drug-tolerant cancer cells and reversing their tolerance therefore provide a promising therapeutic opportunity to impede tumor relapse. 5,10,11 Proteasome inhibitors (PIs) have dramatically improved the treatment of multiple myeloma (MM) and other hematological malignancies, but relapses are frequent and acquired resistance to treatment eventually emerges. 12,13 Mixed-lineage leukemia (MLL), including acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML), is an aggressive hematologic malignancy with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%